AgRuO3, a Strongly Exchange‐Coupled Honeycomb Compound Lacking Long‐Range Magnetic Order. Issue 19 (20th March 2017) - Prasad, Beluvalli E.; Kanungo, Sudipta; Jansen, Martin; Komarek, Alexander C.; Yan, Binghai; Manuel, Pascal; Felser, Claudia
Abstract: Quasi two‐dimensional (2D) oxide‐based honeycomb lattices have attracted great attention for displaying specific electronic instabilities, which give rise to unconventional bonding patterns and unexpected magnetic exchange couplings. The synthesis of AgRuO3, another representative exhibiting unique structural properties, is reported here. The stacking sequence of the honeycomb layers (Ru2 O6 ) differs from analogous precedents; in particular, the intercalating silver atoms are shifted from the middle of the interspaces and cap the void octahedral sites of the (□Ru2 O6 ) slabs from both sides. This way, charge neutral, giant 2D "molecules" of Ag/Ru2 O6 /Ag result; a feature that significantly enhances the overall 2D character of AgRuO3 . Measurements of magnetization have revealed extremely strong magnetic exchange coupling to be present, surviving to a temperature as high as 673 K, which is the temperature of thermal decomposition. No indication for long‐range magnetic order has, however, been observed. Theoretical analyses confirm the pronounced 2D character of the electronic system, and in particular reveal the inter‐honeycomb layer coupling Jc to be distinctly weak. Abstract : Silver lining : AgRuO3 has been synthesized under hydrothermal conditions as a coarse crystalline, single‐phase material. It shows several unique and intertwined properties with respect to crystal structure, magnetic response, and electronic structure.